Radiosurgical treatment of trigeminal neuralgia using the CyberKnife system (Pain medicine, 2020)
Trigeminal neuralgia (TN) is the most common neuralgia, among others. In the Medical Center of Yuriy Spizhenko LLC from 2013 to 2020, 24 patients with TN were treated using the CyberKnife unified robotic system for radiosurgical treatment. This system is the maximum accuracy of
Keywords: trigeminal neuralgia; radiosurgical treatment; CyberKnife